PENGARUH KOMPENSASI, KEPEMIMPINAN, DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA KOPERASI SIMPAN PINJAM (KSP) KARYA MURNI BINJAI - Sinaga, Ria Veronica; Tarigan, Imanuel (Jurnal Manajemen dan Bisnis, 2024)
This research aims to evaluate the influence of compensation, leadership, and work environment on employee job satisfaction at the Cooperative Savings and Loan (KSP) Karya Murni Binjai. With a sample size of 64 individuals, data was collected through questionnaires and interviews, then analyzed using multiple linear regression. The results indicate that compensation, leadership, and the work environment simultaneously have a positive and significant impact on job satisfaction, with an f-value of 22.446 (F-table = 2.31). Partially, compensation (t-value = 3.986), leadership (t-value = 3.716), and the work environment (t-value = 2.035) also show significant effects (t-table = 1.661). A correlation coefficient (r) of 0.745 suggests a strong relationship, and a coefficient of determination (R Square) of 0.555 indicates that these variables can explain 55.5% of job satisfaction variability.Based on these findings, it is recommended to evaluate compensation policies, including reviewing salary levels and incentives, and implementing recognition programs to enhance employee motivation. Leadership training, supportive leadership styles, and mentoring can strengthen the supervisor-subordinate relationship. Evaluating workplace factors, such as improving lighting, temperature, and facilities, and promoting an inclusive work culture, is essential. Providing space for employee input can also enhance overall workplace conditions.